Implementation of Independent Teaching in Network System Administration Teaching Materials at SMK Negeri 2 Makassar - Haldi Alfaisal; Riana Tangkin Mangesa; Sanatang (PT. Global Research Collaboration, 2026)
This article discusses the implementation of Merdeka Mengajar (Independent Teaching) in the Network System Administration teaching material at SMK Negeri 2 Makassar. This study aimed to describe the implementation of Merdeka Mengajar-based network system administration learning at SMK Negeri 2 Makassar, as well as student creativity in the applying Merdeka Mengajar. This was a qualitative descriptive study. Data collection techniques were obtained using observation and interview methods from various sources, namely network system administration teachers and students at SMK Negeri 2 Makassar. Documentation was in the form of photographs of the interview process, school profiles, and learning activities. The results of the study indicate that the implementation of Merdeka Mengajar in network system administration learning at SMK Negeri 2 Makassar has been carried out quite well, although it requires many improvements because various related parties are still in the process of adjustment. This can be seen from the planning stage, implementation stage, and evaluation stage. Supporting factors for the implementation of Merdeka Mengajar-based network learning administration system include: (1) Adequate facilities and infrastructure. (2) Teachers who always strive to improve their competence. As for student creativity in the application of Merdeka Mengajar, the effectiveness of Merdeka Mengajar learning lies in the readiness and learning methods of the students themselves, whether done independently or in groups. Creativity is a key aspect that needs to be considered to develop creative thinking skills, so that students can turn their ideas into real actions that are beneficial.